‘Empty signiﬁer’: The concept of ‘populism’ in the contemporary mainstream political science - L. G. Fishman (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2021)
The paper aims to clarify the origins of contemporary populism, as well as to outline the prospects for further research on this matter. The author examines this phenomenon within the framework of the dominant mainstream in political science. The latter imply the totality of approaches to conceptualization of the key modern social, economic, political and cultural issues. The author advances a hypothesis that both the extreme diversity of the views regarding the nature of populism and the impossibility to develop an all-encompassing deﬁ nition of this paradoxical phenomenon directly stem from the characteristic features of this dominant discourse. The paper shows that this discourse emerged from the overlapping narratives of transition, modernization, free market, unlimited economic growth and ‘the end of history’ and establishes an hierarchy of global knowledge based on three principles: Western dominance, capitalism and liberalism. The author emphasizes that within this theoretical framework non-Western populism is portrayed as a relatively progressive phenomenon, as a means and an indicator of progress towards capitalism and democracy. In this case populism is interpreted as an element of transition to a ‘proper’ Modernity. However, identical political movements, practices and rhetoric of the Western populists are usually portrayed as a deviation from the norm, from Modernity in general and the ideals of liberal democracy in particular. Meanwhile, the paper argues that as Western liberal democracies transform into ‘conciliatory democracies’ (‘oligarchies’) and increasingly resemble ‘defective democracies’, they themselves start to deviate from the normative ideal, just as any regime they label ‘populist’. Therefore, the existing concepts of populism signify not only a certain deviation from the ideal but also the birth of a new reality which cannot be conceptualized within the framework of the contemporary mainstream political science. The concept of populism appears as an ‘empty signiﬁer’ and as a collective term for all inconvenient and troubling social-political phenomena that mainstream political scientists are unable or unwilling to explain.